PEMETAAN DAERAH POTENSI LONGSOR DI KABUPATEN TRENGGALEK MENGGUNAKAN DATA CITRA SATELIT MULTI-TEMPORAL - Maulana, Bustam Fiqor; Taufik, Muhammad (Geoid, 2019)
The use of three satellite imagery data at the same location and different time are 2003, 2013 and 2018, resulting in three potential maps of landslide with different time series of 2003, 2013, and 2018.. Map of potential landslides generated classified in three classes of potential landslide levels. The result of a potential landslide map indicates there is a difference in potential level classes. In the span of years 2003 to 2013 there was a total change in the class of potential levels of 10082.25 hectares of the total area of Trenggalek Regency. From 2013 to 2018 there were a change of 14882.77 hectares. Calculation of correlation between land cover area change with potential landslide change is equal + 1. This value indicates a very strong positive correlation between changes in the area of landslide potential with the change in land cover. The use of three satellite imagery data at the same location and different time are 2003, 2013 and 2018, resulting in three potential maps of landslide with different time series of 2003, 2013, and 2018.. Map of potential landslides generated classified in three classes of potential landslide levels. The result of a potential landslide map indicates there is a difference in potential level classes. In the span of years 2003 to 2013 there was a total change in the class of potential levels of 10082.25 hectares of the total area of Trenggalek Regency. From 2013 to 2018 there were a change of 14882.77 hectares. Calculation of correlation between land cover area change with potential landslide change is equal + 1. This value indicates a very strong positive correlation between changes in the area of landslide potential with the change in land cover.